Digital parenting during the COVID-19 lockdowns: how Chinese parents viewed and mediated young children's digital use. Issue 15 (18th November 2022) - Cao, Simin; Dong, Chuanmei; Li, Hui
ABSTRACT: The COVID-19 lockdowns had forced young children to take digital preschooling and their parents to practize digital parenting. This study explored how Chinese parents viewed and mediated early digital use during the lockdowns. A total of 2491 parents were recruited nationally and surveyed online in late 2020. The results indicated that: (1) Chinese parents held mixed views of early digital use with some being positive (25.09%), and negative (35.13%), and balanced or ambivalent (32.64%); (2) they were concerned about the negative impact on early learning and development even though the lockdown has led to an inevitable surge in digital use; and (3) they mainly perceived parental roles as guides (35.84%) and supervisors (32.04%) and adopted four digital parenting approaches: supervision, active mediation, restrictive mediation, and co-use or co-view. The findings imply that Chinese parents were not ready to cope with the challenges caused by early digital use.